MIGATISAY (MI GAPLEK TULANG IKAN DAN SAYURAN) SOTO GORENG KOYA - Nirmala Nurul Majidah; Rizki Ramadan; Rahmat Yusuf Ferdinan; Nirmala Nurul Majidah; Naila Noviolly Eka Putri (Inisiasi, 2023)
The background of this research is based on the fact that most regions at Wonogiri Regency have many varieties of natural resources that the citizen does not optimally use—for example, the marine and farming sectors. In the nila fish fisheries sector, most people only process the flesh of the fish as food products. In fact, besides the flesh, fish bones also have many benefits. This research aims to make use of fish bones to be an innovation of food products that most people will like and to find out the ingredients benefits of MIGATISAY products. The process of making the noodle is to wash the fish bones and pour lemon juice into it. The third step is to boil the fish bones with high hot pressure for an hour, fourth step is to wash the vegetable to clean, drain it, and soak it in water. The fifth step is to filter the vegetable extract. The research is done to develop any innovation in using nila fish bones by extracting it into powder, and then modifying the powder with cassava flour, and combining it with vegetable extract to make an instant noodle product named MIGATISAY. To make MIGATISAY tastier, we added more innovation called ‘koya’ powder. ‘Koya’ powder is made from the nila flesh added with ‘soto’ powder which we had made. The data of this research is taken with the questionnaire method. The respondents are the people at SMA Negeri 2 Wonogiri and some people around the neighboring area of the school. The respondents answered the questions at the questionnaire which was prepared. The result of the research shows that the noodle which is made from fish bone has some nutrients. Based on the laboratory test which was conducted at UESBE Laboratory, the nutrients in it consist of carbohydrate 78.23%, protein content 5.10 %, fat content 2.25% ash content 5.07%, and water content 9.35%. Based on the test conducted by Dinas Kesehatan Wonogiri about the level of artificial color and preservative in this product is both found as negative.